Do Perverted Justice chat logs contain examples of Overt Persuasion and Sexual Extortion? A Research Note responding to Chiang and Grant (2017, 2018) - Schneevogt, Daniela; Chiang, Emily; Grant, Tim (Language and Law / Linguagem e Direito, 2018)
Studies by Chiang and Grant (2017, 2018) on the rhetorical moves of online child sexual abusers suggest that interactions between offenders and adults posing as children differ in various ways from those between offenders and genuine child victims. They point specifically to the use by one offender of moves identified as Overt persuasion and Extortion in his interactions with real children noting that these were absent from data featuring adults posing as children. The current study investigates whether these more coercive and forceful moves are in fact absent in sexualised interactions between offenders and adult decoys by applying corpus linguistic techniques to a corpus of 622 chat logs. It is shown that overtly persuasive language is rare in the texts, and that no extortion occurred. This finding supports Chiang and Grant’s claim and their assertion that data featuring adult decoys is not truly representative of interactions between child victims and their abusers.